A genome‐wide association study of heat stress‐associated SNPs in catfish. (1st August 2016) - Jin, Y.; Zhou, T.; Geng, X.; Liu, S.; Chen, A.; Yao, J.; Jiang, C.; Tan, S.; Su, B.; Liu, Z.
Summary: Heat tolerance is a complex and economically important trait for catfish genetic breeding programs. With global climate change, it is becoming an increasingly important trait. To better understand the molecular basis of heat stress, a genome‐wide association study (GWAS) was carried out using the 250 K catfish SNP array with interspecific backcross progenies, which derived from crossing female channel catfish with male F1 hybrid catfish (female channel catfish × male blue catfish). Three significant associated SNPs were detected by performing an EMMAX approach for GWAS. The SNP located on linkage group 14 explained 12.1% of phenotypical variation. The other two SNPs, located on linkage group 16, explained 11.3 and 11.5% of phenotypical variation respectively. A total of 14 genes with heat stress related functions were detected within the significant associated regions. Among them, five genes— TRAF2, FBXW5, ANAPC2, UBR1 and KLHL29— have known functions in the protein degradation process through the ubiquitination pathway. Other genes related to heat stress include genes involved in protein biosynthesis ( PRPF4 and SYNCRIP ), protein folding ( DNAJC25 ), molecule and iron transport ( SLC25A46 and CLIC5 ), cytoskeletal reorganization ( COL12A1 ) and energy metabolism ( COX7A2, PLCB1 and PLCB4 ) processes. The results provide fundamental information about genes and pathways that is useful for further investigation into the molecular mechanisms of heat stress. The associated SNPs could be promising candidates for selecting heat‐tolerant catfish lines after validating their effects on larger and various catfish populations.